Effect of Knowledge Management on Firm Performance and Competitiveness - Wanjiru, Anna (European Journal of Information and Knowledge Management, 2022)
Purpose: The purpose of this study was to investigate the effect of knowledge management on firm performance and competitiveness. Theoretical relations are tested through an empirical study carried out on 5 companies. Results: The results showed how the ï¬rms that adopt knowledge management practices obtain better results than their competitors. The research limitations/implications were that the subject of principles has not been considered a dimension of knowledge management. New avenues of inquiry are opened considering this dimension. Unique contribution to theory, practice and policy: The practical implications were that the study only considered practices that have a positive incidence on ï¬rm performance. Further, the conceptualization of knowledge management practices represents atheoretical innovation. This scale can be used in other knowledge-intensive industries. The analysis concludes that knowledge management practices have a positive incidence on ï¬rm performance